Fan Perceptions of Streamer Windah Basudara’s Personal Branding on Youtube - Rossa Dwi Maharani (Nusantara Society Lab, 2025)
This study aims to explore fans perceptions of Windah Basudara's personal branding on the Youtube Platform, the extent to which fans understand the elements of his personal brand, and how they evaluate the self-image constructed by Windah Basudara. This research employed a descriptive quantitative method, with data collected through questionnaires distributed to 100 respondent who are fans of Windah basudara on Youutbe and member of his Discord Community. The data were analyzed using a descriptive approach with a Likert scale. The results indicate that fans perception of Windah Basudara's personal branding falls into the